A core outcome set for clinical studies of adhesive small bowel obstruction. (3rd June 2022) - ,
Abstract: Aim: Adhesive small bowel obstruction (ASBO) is a common surgical emergency condition. Research in the field is plentiful; however, inconsistency in outcome reporting makes comparisons challenging. The aim of this study was to define a core outcome set (COS) for studies of ASBO. Methods: The long list of outcomes was identified through systematic review, and focus groups across different geographical regions. A modified Delphi consensus exercise of three rounds was undertaken with stakeholder groups (patients and clinicians). Items were rated on a 9‐point Likert scale. Items exceeding 70% rating at 7–9 were passed to the consensus meeting. New item proposals were invited in round 1. Individualised feedback on prior voting compared to other participants was provided. An international consensus meeting was convened to ratify the final COS. Results: In round 1, 56 items were rated by 118 respondents. A total of 18 items reached consensus, and respondents proposed an additional 10 items. Round 2 was completed by 90 respondents, and nine items achieved consensus. In round 3, 80 surveys were completed; one item achieved consensus, and five borderline items were identified. The final COS included 26 outcomes, mapped to the following domains: Interventions, need for stoma, septic complications, return of gut function, patient reported outcomes, and recurrence of obstruction, as well as mortality, failure to rescue, and time to resolution. Conclusion: This COS should be used in future studies in the treatment of adhesive SBO. Further studies to define a core measurement set are needed to identify the optimum tools to measure each outcome.